The effect of environmental performance, managerial ownership, and dividend policy on the relative value of a company - Yunarsih, Ni Kadek; Wirama, Dewa Gede; Putra, I Nyoman Wijana Asmara; Sisdyani, Eka Ardhani (International research journal of management, IT and social sciences, 2023)
Relative value of a company is a method of determining the value of an asset by looking at the price of a comparable asset relative to common variables such as income, book value, or sales. The relative value method allows investors to make an equivalent comparison of the values of similar assets. This study aims to examine the environmental performance, managerial ownership and dividend policy on the relative value of a company. The population of this study is all companies that follow the Corporate Performance Rating Assessment Program (PROPER) and have a positive relative value listed on the Indonesia Stock Exchange (IDX) for the period 2019-2021. The sample determination technique uses a saturated sampling technique with a sample number of 70 companies. In this study, the relative value is measured by combining the value of price to book value (PBV), price to earnings ratio (PER) and price to sales ratio (PSR). Environmental performance is measured using PROPER, managerial ownership is measured using managerial ownership (MOWN) and dividend policy is measured using dividend payout ratio (DPR). The data analysis technique used was multiple linear regression analysis.